1982
DOI: 10.1083/jcb.94.2.253
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid induces embryonal carcinoma cells to differentiate into neurons and glial cells.

Abstract: Murine embryonal carcinoma cells can differentiate into a varied spectrum of cell types. We observed the abundant and precocious development of neuronlike cells when embryonal carcinoma cells of various pluripotent lines were aggregated and cultured in the presence of nontoxic concentrations of retinoic acid. Neuronlike cells were also formed in retinoic acid-treated cultures of the embryonal carcinoma line, P19, which does not differentiate into neurons in the absence of the drug. The neuronal nature of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
488
0
9

Year Published

1996
1996
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 761 publications
(511 citation statements)
references
References 44 publications
14
488
0
9
Order By: Relevance
“…P19 cells respond to retinoic acid by di erentiating into neurons, astrocytes and oligodendrocytes (Staines et al, 1996;Jones-Villeneuve et al, 1982). There is a suggestion from p53 de®cient mice that precocious neurogenesis may result from the absence of p53 (Hall and Lane, 1997), a result consistent with the abundant development of neurons from P19 cells.…”
Section: Response To Radiationmentioning
confidence: 96%
“…P19 cells respond to retinoic acid by di erentiating into neurons, astrocytes and oligodendrocytes (Staines et al, 1996;Jones-Villeneuve et al, 1982). There is a suggestion from p53 de®cient mice that precocious neurogenesis may result from the absence of p53 (Hall and Lane, 1997), a result consistent with the abundant development of neurons from P19 cells.…”
Section: Response To Radiationmentioning
confidence: 96%
“…P19, which carries a normal RARa, is growth-inhibited and can differentiate into neurons in response to RA (Jones-Villeneuve et al, 1982;Edwards and McBurney, 1983). In contrast, its mutant counterpart, the RAC65 cell line, is RA-resistant and cannot differentiate when grown as aggregates (Jones-Villeneuve et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The actions of RA are mediated by nuclear receptors (RARs and RXRs) which belong to the steroid/thyroid hormone receptor superfamily and act as ligand-inducible transcription factors (for a recent review see Guiguere, 1994). RA is known to inhibit proliferation and to stimulate morphological di erentiation in neuroblastoma cells Sidell et al, 1983;Kaplan et al, 1993) and to induce neuronal di erentiation of teratocarcinoma cells (Jones-Villeneuve et al, 1982). We have recently shown that RA also profoundly a ects growth, di erentiation and gene expression on PC12 cells .…”
Section: Introductionmentioning
confidence: 99%